Temporal and Spatial Evaluation of Mono(2-ethylhexyl) Phthalate (MEHP) Detection in Common Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA - Miranda K. Dziobak; Brian C. Balmer; Randall S. Wells; Emily C. Pisarski; Ed F. Wirth; Leslie B. Hart (Oceans, 2022)
Phthalates are endocrine-disrupting chemicals added to plastics, personal care products, cleaning solutions, and pesticides. Extensive use has led to its exposure to wildlife, including common bottlenose dolphins (Tursiops truncatus) from Sarasota Bay, Florida, USA; however, there are gaps in knowledge regarding whether sample timing or geographic location influence exposure. Dolphins were evaluated for temporal and spatial variability in urinary mono(2-ethylhexyl) phthalate (MEHP) detection (2010–2019). Significant fluctuations in detectable MEHP concentrations were found across the dataset. All samples from 2014 and 2015 (n = 12) had detectable MEHP concentrations; thus, data were classified into cohorts to explore the significance of prevalent MEHP detection (“Cohort 1” (n = 10; 2010–2013), “Cohort 2” (2014–2015), and “Cohort 3” (n = 29; 2016–2019)). Compared to Cohorts 1 and 3, Cohort 2 had higher detectable MEHP concentrations (Dunn’s; p = 0.0065 and p = 0.0012, respectively) and a greater proportion of detectable MEHP concentrations (pairwise comparisons using Benjamini–Hochberg adjustments: p = 0.0016 and p = 0.0059, respectively). MEHP detection also varied across spatial scales. Dolphins with detectable MEHP concentrations had ranges primarily within enclosed embayments, while dolphins with nondetectable MEHP concentrations extended into open waters, potentially indicating geographically linked exposure risk. This study suggests that researchers and management agencies should consider a population’s ranging pattern, geographic habitat characteristics, and sample timing when assessing small cetacean health in relation to contaminant exposure.

Antibiotics as CECs: An Overview of the Hazards Posed by Antibiotics and Antibiotic Resistance - Geoffrey I. Scott; Dwayne E. Porter; R. Sean Norman; C. Hart Scott; Miguel I. Uyaguari-Diaz; Keith A. Maruya; Steve B. Weisberg; Michael H. Fulton; Ed F. Wirth; Janet Moore; Paul L. Pennington; Daniel Schlenk; et al. (Frontiers in Marine Science, 2016)

An assessment of benthic condition in several small watersheds of the Chesapeake Bay, USA - Andrew K. Leight; Ward H. Slacum; Ed F. Wirth; Mike H. Fulton (Environmental Monitoring and Assessment, 2011)